2014
DOI: 10.1016/j.annepidem.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Very low maternal lead level in pregnancy and birth outcomes in an eastern Massachusetts population

Abstract: Purpose Maternal lead exposure is associated with poor birth outcomes in populations with moderate to high blood levels. However, no studies have looked at exposure levels commonly experienced by US women. Methods We evaluated the relationship between maternal red blood cell (RBC) lead levels in mid-pregnancy and birth outcomes in 949 mother-child pairs in a pre-birth cohort. We used multiple linear regression and logistic regression, adjusted for potential confounders including maternal age, race, pre-pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 32 publications
7
39
2
1
Order By: Relevance
“…However, in our study, approximately 9.2 % of all the pregnant women had a blood Pb level C70 lg/L. In comparison to previous studies, the present study determined higher levels of Pb at periods of pregnancy [18]. Therefore, a careful inspection of pregnant women's homes for environment sources of Pb is important in protecting them against continual exposure.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…However, in our study, approximately 9.2 % of all the pregnant women had a blood Pb level C70 lg/L. In comparison to previous studies, the present study determined higher levels of Pb at periods of pregnancy [18]. Therefore, a careful inspection of pregnant women's homes for environment sources of Pb is important in protecting them against continual exposure.…”
Section: Discussioncontrasting
confidence: 77%
“…Lead is a nonessential nutrient element in the body and the ideal content of lead in the human body is zero. Maternal lead exposure, even at very low levels, may adversely affect some childbirth outcomes [18]. However, in our study, approximately 9.2 % of all the pregnant women had a blood Pb level C70 lg/L.…”
Section: Discussionmentioning
confidence: 82%
“…Other metals were not statistically significantly associated with birth weight or gestational age. Studies have reported a potential link between metal concentrations measured in blood samples and birth weight and gestational weeks, particularly for Pb, As, and Cd, but the results have been inconsistent Ikeh-Tawari et al 2013;Perkins et al, 2014;Vall et al, 2012). However, no study to date has investigated the relationship between metals in indoor air and adverse birth outcomes.…”
Section: Carcinogenic Riskmentioning
confidence: 91%
“…Specifically, maternal exposure to lead and mercury may contribute to increased risk of spontaneous abortion [24] and preterm delivery [5, 6]. Exposure to lead and mercury is widespread in US and Mexican populations [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…This study aimed to identify miRNAs that were significantly associated with i) blood lead, ii) patellar or tibial bone lead, or iii) toenail mercury. Lead was selected as a prioritized metal of interest based on previously observed associations between prenatal lead exposure and preterm birth [6, 25, 26]. Mercury was also prioritized since limited literature suggests a relationship may exist with increased preterm birth risk [5].…”
Section: Introductionmentioning
confidence: 99%